2008
DOI: 10.1590/s0036-46652008000200004
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus in colorectal cancer and idiopathic ulcerative colitis

Abstract: SUMMARYCytomegalovirus (CMV) is a genus in the family Herpesviridae that has been associated with gastrointestinal syndromes. In this work we looked for a possible association of CMV infection with colorectal cancer and ulcerative colitis (UC). Blood and enteric tissue samples of 14 patients with colorectal cancer and of 21 with UC were subjected to a nested-PCR that amplifies part of the gB gene of CMV and also to immunohistochemistry using a specific monoclonal antibody to IE 76kDa protein of CMV. CMV was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…However, taken along with other studies finding a deleterious impact of mCMV on colitis [9, 11, 13-17, 19-21, 28], we suggest that although small, the changes we detected may be meaningful, and set the stage for future studies into underlying mechanisms, in particular the aspect of enhanced bleeding. Another potentially important consideration in designing future studies is addressing the possible link between steroid-resistant UC and HCMV.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, taken along with other studies finding a deleterious impact of mCMV on colitis [9, 11, 13-17, 19-21, 28], we suggest that although small, the changes we detected may be meaningful, and set the stage for future studies into underlying mechanisms, in particular the aspect of enhanced bleeding. Another potentially important consideration in designing future studies is addressing the possible link between steroid-resistant UC and HCMV.…”
Section: Discussionsupporting
confidence: 74%
“…However, the link between HCMV and UC is stronger [13-18]. The virus is prevalent in tissues of these patients [19] and reactivation of the virus in UC patients is associated with steroid-resistance during treatment [16]. The exact role of CMV in IBD is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CMV DNA (34,37,38) or CMV antigens (34, 39) have been detected in colon tumors and in cell lines derived from them, but this association has not been universally confirmed (40)(41)(42)(43)(44)(45)(46), perhaps due to the different sensitivities of the methods used for detection of CMV in the different studies (41,43,47,48). Several reports have shown that CMV infection may interfere with key cellular signaling pathways, leading to enhanced survival and angiogenesis, and that it may also alter cell motility and adhesion (49).…”
Section: Figurementioning
confidence: 99%
“…Currently IHC is considered the gold standard for detecting CMV [7]. In fact, the prevalence of colonic CMV has been reported to be as high as 14-57% in patients with IBD who had IHC examination [8][9][10]. However, this is not routinely done in general practice.…”
mentioning
confidence: 99%